New Jacobi Elliptic Function Solutions for the Generalized Nizhnik-Novikov-Veselov Equation (Communications in Mathematical Research, 2021)
In this paper, a new generalized Jacobi elliptic function expansion methodbased upon four new Jacobi elliptic functions is described and abundant solutions ofnew Jacobi elliptic functions for the generalized Nizhnik-Novikov-Veselov equationsare obtained. It is shown that the new method is much more powerful in finding newexact solutions to various kinds of nonlinear evolution equations in mathematicalphysics.